The Falsification of Land Sale and Purchase Deed Date by Land Deed Making Officer in Yogyakarta - Damayanti, Salsabila Prajna (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
This research describes the responsibility of the Land Deed Making Officer (PPAT) and the legal protection for the parties for the forgery of the sale and purchase deed made by PPAT by postponing the date of the deed. The forgery is done to make it appear as if it does not require a court order and the approval of the guardian. In the execution of the deed, there is interference from the buyer who has bad faith by forcing the seller to sign the deed of sale and purchase first before the payment is fully paid. The type of research used is Doctrinal. The result of the analysis of this research is that PPATs who are negligent in carrying out their obligations in making deeds resulting in losses for the parties can be subject to civil suits for losses as legal protection for the parties whose names are listed in the deed. In addition, PPAT is also subject to criminal sanctions for violations of Article 263 of the Criminal Code and administrative sanctions regulated in Article 13 paragraph (1) Permen ATR/KBPN Number 2 of 2018, Article 39 paragraph (1) letter c of PP 24/1997, and Article 3 of the IPPAT Code of Ethics.